SIGNIFIKANSI PEMAHAMAN MAKNA HADIS MELALUI ILMU MA’ANI AL-HADIS DALAM AJARAN ISLAM DI ERA KONTEMPORER - Nashih, Nashrulloh Rohmat; Fazri, Taufik; Aylia, Nur Laela; Sholihat, Isna Fauziah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
This document highlights the significance of understanding the meaning of hadith in Islamic teachings and the important role of Hadith Science in analyzing hadith textually and contextually. This study uses the library research method to describe and analyze the subject matter from various related sources. With a deep understanding of the Science of Ma'ani Al-Hadith, it is expected to enrich the knowledge of Muslims about the teachings contained in the traditions of the Prophet Muhammad SAW. It paves the way for a broader understanding of the messages hidden in the traditions, enabling Muslims to deepen their religious beliefs and practices. By emphasizing the importance of context and meaning, Ma'ani Al- Hadith helps maintain the continuity and authenticity of Islamic teachings in the face of dynamic times. In conclusion, the advancement of the Science of Ma'ani Al-Hadith plays an important role in preserving Islam's intellectual heritage and enriching people's understanding of their religion.